ACTION-RELATED THOUGHTS AND BELIEFS REGULATE THE EFFECT OF AGE STEREOTYPES ON AGING PREPARATION - Kim-Knauß, Yaeji; Lang, Frieder; Fung, Helene; Tse, Dwight (INNOVATION IN AGING, 2021)
CRIS-Team WoS Importer:2022-09-16

An Agentic Perspective on Aging Preparation - Kim-Knauß, Yaeji (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)

AN AGENTIC PERSPECTIVE ON AGING PREPARATION - Kim-Knauß, Yaeji; Lang, Frieder (2023)

Consumers' consciousness of health-friendly products and services and its association with sociodemographic characteristics and health status: a cross-sectional survey of the South Korean population - Yun, Young Ho; Sim, Jin Ah; Kim, Yaeji; Lee, Sujee; Kim, Kyoung Nam (BMJ Open, 2020)
OBJECTIVES: To identify consumers' consciousness of health-friendly products and services (consumer reaction, purchase intention and willingness to pay more) and its association with sociodemographic characteristics and multidimensional health status. METHODS: From March to May 2018, we administered questionnaires to 1200 individuals from the general Korean population asking about their perception of health-friendly labels, and if they would purchase such labelled products (foods, pharmaceuticals, etc) and services (purifying water, preventing air pollution, etc) at extra cost. RESULTS: The participants placed a high value on the importance of mental, social, spiritual and physical health factors in terms of the company's products and services with a score of about 8 out of 10 (range, 7.74-8.33). Most respondents (72.4%) said that they were interested in adopting health-friendly labels. When a health-friendly label is introduced (such as one by the Business for Social Responsiveness), 65.1% of the respondents said that they intended to purchase the product or service, while 6.8% said that they did not and 75.0% said that they were willing to pay extra for the health-friendly product or service. Multivariate logistic regression models showed urban residence, high education level and good social health to be significantly associated with positive attitudes towards health-friendly labels. People with high income, no religion or normal weight were more likely to say that they intend to purchase products and services with health-friendly labels. They also had a more positive attitude towards paying more for such products and services, as did people with good spiritual health. CONCLUSION: This study provides data that illustrate the importance of health-friendly products and services to the general population and companies.
CRIS-Team Scopus Importer:2020-06-30
Keywords: health services administration & management; public health; quality in health care

COVID-19 Worries Predict Aging Preparation: Culture- and Domain-Specific Perspectives - Kim-Knauß, Yaeji; Lang, Frieder; Rupprecht, Fiona; Martin, Kristina; Fung, Helene H. (The journals of gerontology. Series B, Psychological sciences and social sciences, 2022)
OBJECTIVES: We investigated whether worrying about coronavirus disease 2019 (COVID-19) predicts people's engagement in aging preparation. Furthermore, we expected that this association would have culture- (i.e., Hong Kong and Germany) and domain-specific (i.e., finances, housing, care needs, connectedness, and end-of-life) tendencies, as the culture and domains that are most severely hit by the pandemic differ. METHODS: A total of 360 and 1,294 adults (aged 18-98 years) living in Hong Kong and Germany, respectively, participated in a web-based study. We fitted our data to a multilevel model in order to take into account the interdependence of domains (i.e., Level 1) within the same individual (i.e., Level 2). RESULTS: The results revealed that reporting higher COVID-19 worries were associated with pandemic-induced aging preparation, and this association was particularly apparent for Germans in comparison to those from Hong Kong. When domains were specified, this cultural difference appeared significantly stronger for the domains of care, connectedness, and end-of-life than finances and housing. DISCUSSION: Findings imply that worrying about the COVID-19 pandemic predicts people to engage in aging preparation particularly in the culture and domains most affected by the pandemic. These results from those worried about the virus may be attributed to the increased self-relevance to the topic and hence motivation.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Coping behavior; End-of-life; Future care needs; Social relations

For a better me? Or for a better us? Perceived utilities of aging preparatory activities and positive future thinking in Germany, USA and Hong Kong - Kim-Knauß, Yaeji; Lang, Frieder; Rohr, Margund K.; Fung, Helene H. (European Journal of Ageing, 2019)
Engaging in aging preparatory activities that is perceived to be utile for oneself (e.g., to retain autonomy and independence) and for others (e.g., to retain a harmonious relationship with important others) may have a functional effect on one’s aging process. We examined how perceived self- and other-related utilities of aging preparatory activities were associated with positive future thinking across adulthood, and whether these associations differed by culture. Building upon cross-sectional data from a web-based study conducted in Hong Kong (n = 283, Mage = 55.12, aged 18–85 years), the USA (n = 264, Mage = 51.06, aged 20–85 years) and Germany (n = 402, Mage = 51.65, aged 19–90 years), we observed different patterns of associations across these three cultures. Perceiving self-related utilities was linked to positive future thinking in the USA and Germany, but not in Hong Kong. In contrast, perceiving other-related utilities of aging preparatory activities was positively associated with future thinking in Hong Kong, but not in the USA or Germany. Perceived risks, on the other hand, showed a negative association with positive future thinking across all cultures. Findings suggest that there might be a culture-specific tendency for individuals to appraise their future, based on their perceived self- or other-related utilities of aging preparatory activities.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Aging preparatory activities; Cross-cultural study; Culture; Perceived risks; Perceived utilities; Positive future thinking; Self-construal

IS THERE A WORRY ADVANTAGE? THE ROLE OF FEAR OF LONELINESS IN OLD AGE IN LONELINESS PREVENTIVE ACTIVITIES - Degen, Nora Marie; Kim-Knauß, Yaeji; Lang, Frieder (2023)

Late-Life Preparedness and Its Correlates: A Behavioral Perspective on Preparation - Kim-Knauß, Yaeji; Lang, Frieder (Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 2021)
Objectives: The present study examined the extent of late-life preparedness and its correlates. In accordance with behavior theories, we postulated that those who have prior experience with caregiving and who perceive such activities as more useful and less risky are more likely to engage in late-life preparatory activities. Because the perceived distance until agingrelated life challenges become prevalent may play a role in late-life preparedness, we hypothesized that the effects of the correlates would vary depending on one's subjective remaining life expectation (SRLE).
CRIS-Team WoS Importer:2021-10-08

Leveraging Text Mining Approach to Identify What People Want to Know About Mental Disorders From Online Inquiry Platforms - Park, Soowon; Kim-Knauß, Yaeji; Sim, Jin Ah (Frontiers in Public Health, 2021)
Online inquiry platforms, which is where a person can anonymously ask questions, have become an important information source for those who are concerned about social stigma and discrimination that follow mental disorders. Therefore, examining what people inquire about regarding mental disorders would be useful when designing educational programs for communities. The present study aimed to examine the contents of the queries regarding mental disorders that were posted on online inquiry platforms. A total of 4,714 relevant queries from the two major online inquiry platforms were collected. We computed word frequencies, centralities, and latent Dirichlet allocation (LDA) topic modeling. The words like symptom, hospital and treatment ranked as the most frequently used words, and the word my appeared to have the highest centrality. LDA identified four latent topics: (1) the understanding of general symptoms, (2) a disability grading system and welfare entitlement, (3) stressful life events, and (4) social adaptation with mental disorders. People are interested in practical information concerning mental disorders, such as social benefits, social adaptation, more general information about the symptoms and the treatments. Our findings suggest that instructions encompassing different scopes of information are needed when developing educational programs.
CRIS-Team Scopus Importer:2021-11-05
Keywords: latent Dirichlet allocation; mental disorder; online inquiry; text mining; topic modeling

PANDEMIC-RELATED SOCIAL RESTRICTIONS INCREASED THE URGENCY AND ENGAGEMENT IN OLD-AGE PREPARATION - Kim-Knauß, Yaeji (INNOVATION IN AGING, 2022)
CRIS-Team WoS Importer:2023-03-10

The Paradox of Aging-Related Fears: Fear of Loneliness in Old Age as a Motivator for Loneliness Preventive Activities - Kim-Knauß, Yaeji; Degen, Nora Marie; Lang, Frieder (Gerontology, 2024)
Introduction: Aging is often seen as a challenging process, prompting individuals to form emotional reactions in response to the perceived challenges associated with growing older, manifested as aging-related fears. The present study focuses on the fear of loneliness in old age, a significant concern considering the socioemotional importance of close relationships in later life. Drawing from proactive coping theory, the study explores the association between fear of loneliness and aging preparation. This research aimed to investigate whether the fear of loneliness motivates individuals to engage in activities aimed at preventing loneliness in old age. For exploratory purposes, we consider both linear and nonlinear effects at the interindividual level, as well as the intraindividual-level differences between fear levels and behavioral outcomes. In addition, we also investigate the moderating role of trait neuroticism in these associations. Methods: Data from the "Ageing as Future (AAF)"project in Germany (N = 1,183) spanning from 2012 to 2023 were utilized. A multilevel model considered both intra- and interindividual variations, incorporating timevarying variables and covariates. Results: Linear mixed model analysis revealed that increased fear of loneliness corresponded to heightened engagement in preventive activities linearly, while a quadratic term indicated an inverted U-shaped relationship. The inclusion of occasionspecific deviation scores showed that individuals were more inclined to engage in preventive activities when experiencing heightened fear of loneliness than usual. This impact of deviation in fear perception was particularly evident among those with high levels of trait neuroticism. Conclusion: The study reveals that fear of loneliness in old age is associated with proactive engagement in preventive activities, with those prone to higher levels of fear or worry being particularly affected. These results emphasize the importance of a moderate level of fear in driving action without succumbing to excessive pessimism or unrealistic optimism. The findings contribute to understanding the motivational role of aging-related fears and hold implications for gerontological practices, emphasizing the need for a balanced fear perception in addressing potential negative impacts of aging. Future research could explore moderators and long-term consequences of motivational aging-related fears.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Aging preparation; Aging-related fears; Loneliness; Preventive activities; Trait neuroticism

“Time without you”: Transition to widowhood and its impact on time perspective and attitudes toward the future - de Paula Couto, M. Clara; Kim-Knauß, Yaeji; Rothermund, Klaus; Fung, Helene H.; Hess, Thomas M.; Lang, Frieder (European Journal of Ageing, 2025)
Widowhood is a significant life event that can profoundly alter an individual’s perception of time. Those who have lost a spouse often find themselves reflecting on past memories, while simultaneously feeling disconnected from the present. However, the impact of widowhood on one’s experience and perception of time has not been thoroughly explored. In this study, we investigate changes in time perspective during the transition to widowhood using a multidimensional approach to temporal experience. This perspective enriches the existing literature, which has primarily focused on the predictive role of time perspective by providing new insights into how major life events can reshape an individual’s experience of time. The sample was drawn from seven measurement points between 2009 and 2023 in the Aging-as-Future longitudinal study. It consisted of 1357 participants aged 50 and older who either remained married throughout the study period (n = 1270) or transitioned to widowhood (n = 87). We assessed four facets of time perspective: past-orientation, feelings of obsolescence, concreteness of the future time, and attitudes toward life’s finitude as well as subjective life expectancy. While the transition to widowhood predicted an increase in past-orientation and in feelings of obsolescence, it predicted a decrease in concreteness of the future. Spousal loss did not influence individuals’ attitudes toward finitude, but those experiencing widowhood reported a decrease in their perceived remaining lifetime. Our study showed that widowhood may lead to shifts in time perspective. Findings underscore the value of considering time perspective as a key indicator of an individual’s adjustment and functioning in response to a major life event.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Critical life events; Fixed-effects panel regression models; Spousal loss; Subjective remaining life expectancy; Time perspective